Texture analysis of second‐harmonic‐generation images for quantitative analysis of reticular dermal collagen fibre in vivo in human facial cheek skin - Ogura, Yuki; Tanaka, Yuji; Hase, Eiji; Yamashita, Toyonobu; Yasui, Takeshi (Experimental dermatology, 2019)
Second‐harmonic‐generation (SHG) microscopy is a powerful tool for in vivo visualisation of collagen fibres in human skin because of its specific collagen selectivity without the need for staining, non‐invasiveness and high‐resolution three‐dimensional imaging. Although texture analysis of SHG images is a promising method for the quantitative analysis of well‐orientated collagen fibre structure in the tendon and cornea, there are few attempts to assess cutaneous ageing. In this study, we applied two texture analysis techniques, namely autocorrelation (2D‐AC) analysis and two‐dimensional Fourier transform (2D‐FT), to evaluate the age‐dependent changes in reticular dermal collagen fibres in in vivo human cheek skin. Age‐dependent changes in the reticular dermal collagen fibres of female subjects in their 20s, 40s and 60s clearly appeared in these texture analyses. Furthermore, the parameter from 2D‐AC analysis showed a significantly higher correlation with skin elasticity measured by a Cutometer®. These results clearly indicate that 2D‐AC analysis of SHG images is highly promising for the quantitative evaluation of age‐dependent change in facial collagen fibres as well as skin elasticity. An appropriate texture analysis will help to provide quantitative insight into collagen fibre structure and will be useful for the diagnosis of pathological conditions as well as cutaneous ageing in skin.